The party-list system as a policy mechanism for popular participation - Cuyco, Onesimo L. (1999)
The trends towards the democratization of governance enhanced the role of civil society in the post-Marcos era. The slogan on people empowerment in all governmental functions has become a buzzword which expresses urgent concerns on the different sectors most especially the marginalized one. When the Marcos charter was changed , various reforms were incorporated to the Freedom Constitution, on of them was the introduction of the party-list system wherein 20% of the composition of the House of Representatives have to come from the party-list of registered sectoral groups or organizations. In 1995,an enabling law was passed providing for a mechanism to the party-list system through Republic Act No. 7941. The law provides a mechanism of proportional representation in the election of representatives to the Lower House where those marginalized or underrepresented sectors, organizations, and parties who lack well-defined political constituencies could contribute in the formulation of appropriate legislations. Empowering them in the House is expected to reap benefits for special interests of the labor, peasants, urban poor, indigenous cultural communities, the elderly, handicapped, women, youth overseas workers, fisherfolks, veterans and the professionals. Three years after, during the May 1998 elections, the system was first implemented. The general impression was that there was a failure of implementation. Common justification cited was the non-filling up of 52 seats allotted by the Constitution by virtue of the RA No. 9741 and the non-broadening of the marginalized sector's representation.